2006
DOI: 10.1007/s11269-006-9095-2
|View full text |Cite
|
Sign up to set email alerts
|

Increase of River Base Flow by Hydropower Gate Operation for Mitigation of CSO Impacts – Potential and Limitations

Abstract: In this paper the measure of increased river base flow is developed and evaluated. Aim is the temporal increase of flow in manmade low flow stretches for sufficient dilution of downstream acute pollution introduced by combined sewer overflows (CSOs). The increase of flow is done by operating upstream located retaining structures such as hydropower intakes. For implementation both energy producers and municipalities are required to cooperate. Thus the measure fits into a core aim of the Water Framework Directiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Nowadays with the available technology, like enhanced radar (Fang et al 2008;Shih et al 2008), such a weather forecast is very possible to be confirmed. Of course, instrumentation used to (rain gauges, radar, etc) and methods applied for forecasting (numerical weather prediction, nowcasting, extrapolation techniques, etc) influence the quality of the forecast (Achleitner and Rauch 2007). In this paragraph we study the case that the weather forecasts are not confirmed and the rainfall does not happen (null rain).…”
Section: Scenario 3 the Weather Forecast Of A Great Rainfall Is Not mentioning
confidence: 99%
“…Nowadays with the available technology, like enhanced radar (Fang et al 2008;Shih et al 2008), such a weather forecast is very possible to be confirmed. Of course, instrumentation used to (rain gauges, radar, etc) and methods applied for forecasting (numerical weather prediction, nowcasting, extrapolation techniques, etc) influence the quality of the forecast (Achleitner and Rauch 2007). In this paragraph we study the case that the weather forecasts are not confirmed and the rainfall does not happen (null rain).…”
Section: Scenario 3 the Weather Forecast Of A Great Rainfall Is Not mentioning
confidence: 99%